2010
DOI: 10.1061/(asce)he.1943-5584.0000238
|View full text |Cite
|
Sign up to set email alerts
|

Urban Runoff Mitigation by a Permeable Pavement System over Impermeable Soils

Abstract: En el centro fundacional de Usaquén, la zona del mercado de pulgas es uno de los lugares más representativos de la ciudad, cuya espacialidad se basa en arquitectura efímera, esta zona posee cualidades espaciales que no responden correctamente a las dinámicas urbanas existentes. El cual, durante los fines de semana la calle tiene altas y variadas dinámicas urbanas, con calidad del espacio público óptima. Pero entre semana, estos mismos espacios son zonas desoladas, con mínimos porcentajes de caminabilidad y seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(165 citation statements)
references
References 11 publications
5
150
0
3
Order By: Relevance
“…This flow takes place after initial fracture flow and before the matrix and fracture pressures equilibrate (Bai et al, 1994). Several studies have demonstrated the long tailing from permeable pavements in discharge hydrographs (e.g., Brattebo and Booth, 2003;Fassman and Blackbourn, 2010) and attributed this effect to the storage and flow through the base and sub-base layers.…”
Section: Theorymentioning
confidence: 99%
“…This flow takes place after initial fracture flow and before the matrix and fracture pressures equilibrate (Bai et al, 1994). Several studies have demonstrated the long tailing from permeable pavements in discharge hydrographs (e.g., Brattebo and Booth, 2003;Fassman and Blackbourn, 2010) and attributed this effect to the storage and flow through the base and sub-base layers.…”
Section: Theorymentioning
confidence: 99%
“…Abbott and Comino-Mateos (2003) measured the outflow from a car park with a permeable pavement system and found that on average, only 22.5% of runoff leaves the system during a storm, and that a 2-h storm event takes two days to drain out of the system. Fassman and Blackbourn (2010) found that the peak flow from a permeable pavement underdrain is less flashy and tends to show less variation overall than that from asphalt surface during storms. Chapman and Horner (2010) reported that a street-side bioretention facility in Washington can achieve 26e52% of runoff retention in real-weather conditions.…”
Section: Introductionmentioning
confidence: 97%
“…This is due to a delayed response in the matrix to pressure head changes that occur in the surrounding fractures. Brattebo and Booth (2003), Brunetti et al (2016b), andFassman et al (2010) observed a similar behavior in permeable pavements, the base and sub-base layers of which are composed of crushed stones. In such circumstances, more complex models are needed to simultaneously describe fast preferential flow and the matrixfracture interactions in the filter layer (Brunetti et al, 2016b).…”
Section: Kriging-based Optimizationmentioning
confidence: 64%